AB0335 PATIENTS IN REMISSION FREE OF DIRECTED BIOLOGICAL / SYNTHETIC DRUG. ANALYSIS OF A COHORT OF PATIENTS TREATED BY OBJECTIVES IN OPTIMIZATION FOR 6 YEARS. (13th June 2020) - Castro, P.; Aragón, A.
Abstract : Background: The goal of treatment with biological DMARDs (bDMARDs) should be the use for a limited period of time, during the called "therapeutic window of opportunity" to induce disease remission, followed by the maintenance of low activity with conventional DMARDs. We study if we achieve this goal in a cohort of patients treated by objectives in the last 6 years. Objectives: To assess the frequency and characteristics of patients with rheumatoid arthritis (RA), spondyloarthropathies (SA) and psoriatic arthritis (PsA)) treated with FB / SD who achieve remission without FB / SD. Methods: Observational and prospective study, which included a cohort of patients with RA, SA and PsA treated by objectives with FB / SD and optimized from January 2014 to December 2019. Optimization, defined as the reduction or prolongation of the interval of at least one dose, it was indicated when patients had received> 6 months of treatment and were in clinical remission / low activity defined as DAS28 <3.2 for RA and PsA, and BASDAI <4 for SpA. All patients who managed to maintain remission without receiving FB / SD were also collected. Results: A total of 260 patients (115 RA, 69 SA and 76 PsA) were included in the study. Of the total of these patients, 32.7% received at least two treatments ("switch"). Of all the patients, 53% were optimized and according to the diagnosis: 60.9% had RA, 52.2% SA and 39.4% PsA. 5.3% of the patients were free of FB / SD: 5 patients with RA (4.34%), 8 patients with SA (11.6%) and 1 patient with PsA (1.3%). Among patients who entered clinical remission without FB / SD, 57% had received only one treatment with FB / SD while 43% of the patients had received two or more FB / SD. Only 3 of the patients with RA and 1 patient with PsA managed to be free of treatment without FB / SD or conventional DMARD. Conclusion: Remission without FB / SD treatment was rare, being higher in SA than in RA and in PsA, maintaining the same severity and frequency patterns in achieving optimization according to different pathologies (EspA> AR> APs). Except in the APs, more than 50% of the patients with RA and SA entered into optimization. Clinical remission without FB / SD was less frequent in the PsA probably because the MDA is more demanding than the other outcome measures and because it is a more complex and heterogeneous disease with domains controlled by various cytokines. Patients with disease-free RA or APs without FB / SD or conventional DMARD were the exception. Disclosure of Interests: None declared